A NIR-II fluorescent probe for articular cartilage degeneration imaging and osteoarthritis detection. (10th January 2019) - Yi, Wanrong; Zhou, Hui; Li, Anguo; Yuan, Ying; Guo, Yaqi; Li, Pengcheng; Qi, Baiwen; Xiao, Yuling; Yu, Aixi; Hu, Xiang
Abstract : A Type II collagen-binding peptide based NIR-II fluorescent probe for articular cartilage degeneration imaging and early osteoarthritis detection. Abstract : Articular cartilage (AC) is a complex water-bearing tissue consisting of chondrocytes, proteoglycans, and collagen. AC degeneration, which occurs in the early stage and throughout the entire course of osteoarthritis (OA), is one of the main pathological changes of OA. However, current clinical approaches are unable to detect AC degradation during the early stage of OA. Herein, a novel NIR-II probe, CH1055-WL, was developed with an organic fluorophore (CH1055) and type II collagen-binding peptide (WYRGRL) for AC targeting and degeneration imaging. In vitro and in vivo imaging studies demonstrated thatCH1055-WL specifically bound to AC and permitted sensitive detection of age-related or surgically induced AC degeneration in living mice. In vitro imaging of cartilage samples from pig knee joint and in vivo imaging of live mice with the probe administered via local injection in joint cavities demonstrated thatCH1055-WL specifically and efficiently bound to AC. Further evaluation ofCH1055-WL revealed sensitive detection of age-related AC degeneration and surgically induced AC degeneration in living mice. Our results indicated that the cartilage-targeting probeCH1055-WL allowed visual monitoring of AC degeneration in living subjects, thus displaying promise for early OA detection.